Describing the intestinal microbiota of Holstein Fasciola-positive and -negative cattle from a hyperendemic area of fascioliasis in central Colombia (2021)
The ability to identify compositional changes in the intestinal microbiota of parasitized hosts is important for understanding the physiological processes that may affect animal productiv ity. Within the field of host–parasite interactions, many studies have suggested that hel minths can influence the microbial composition of their hosts via their immunomodulatory effects. Bovine fascioliasis is a helminthiasis widely studied by immunologists, but with little information available regarding gut microbial communities. Thus, we aimed to describe the composition of the intestinal microbiota of Holstein Fasciola-positive and -negative cattle using parasitological methods and ELISA (enzyme-linked immunosorbent assay). Bovine fecal samples (n = 65) were obtained from livestock slaughter plants in the Cundi-Boya cense Colombian highlands (a hyperendemic region for bovine fascioliasis) and studied by amplicon-based next-generation 16S-rRNA and 18S-rRNA gene sequencing. From these samples, 35 were Fasciola hepatica-negative and, 30 were F. hepatica-positive in our detection analysis. Our results showed a reduction in the relative abundance of Bacteroi detes and Ascomycota in the Fasciola-positive samples, along with decreased relative abundances of the commensal taxa previously associated with fermentation and digestion processes. However, metabolomic approaches and functional analyzes of the intestinal microbiota are necessary to support these hypothesis. These findings are a small first step in the development of research aimed at understanding how microbial populations in bovines are modulated in liver helminth infections.